الفرضيات الجدلية لكوفيد-19 ما بين نظرية المؤامرة والمقاربة الإيكولوجية - عبدالعزيز، سوزي محمد رشاد (جامعة القاهرة - كلية الاقتصاد والعلوم السياسية, 2021)
تشكل لحظة انتشار الأوبئة، مثل فيروس كورونا المستجد بيئة خصبة لتصاعد التفكير التآمري، ربما أكثر حدة مقارنة بأوقات الأزمات والتغيرات التاريخية الكبرى وذلك لأن خطر البقاء يصبح أكثر ضغطا على ذهنيات الأفراد والجماعات وحتى الحكومات بما قد يدفعهم للميل إلى تبني أفكار وتصورات وربط الأحداث والقفز إلى النتائج دون فحص كاف للمقدمات. وتزداد فرص ذلك الانتشار في وجود حواضن للمؤامرة، كالتضليل المعلوماتي، والاتهامات المتبادلة بين الدول حول المسؤولية عن نشر الفيروس، بخلاف الصراع العالمي الذي يؤسس له مناصرو العالمية حول المؤامرة الكبرى لكيانات لها مصالح حول العالم قد تكون متورطة في المؤامرة، وفي مقابل تلك التفسيرات تظهر العقلية العلمية التي ترتكن على الدراسات والدلائل العلمية، بل وتتنبأ بالأحداث المستقبلية في ظل معطيات محددة والتي أشارت إلى أن تدمير النظم الأيكولوجية يعزز فرص انتشار الفيروسات من الحيوانات إلى البشر، خاصة أنها قد لا تجد عوائل في البيئة التي تظهر فيها، كما أن استمرار ذلك التدمير البيئي قد يدفع إلى ظهور جوائح أشد شراسة بسبب فيض عدوي الجراثيم وانبثاقاتها، وبالتالي فهذه المقالة هي استجابة لخطر وباء COVID-19 الأخير حيث تؤكد على الدور الذي يمكن أن تلعبه مناهج العلوم الاجتماعية في تقييم أسباب المخاطر والاتجاهات المختلفة في تفسيرها من خلال المقاربات العقلانية rational approaches في فهم الظاهرة، وتجنب المقاربات التآمرية."
The moment of pandemics outbreak like new corona virus represents a rich environment for the escalation of the conspiratorial thinking. It may be more intensive compared with the times of crises and great historical changes, because the danger of existence has become more stressing on the mentality of individuals, groups, and even governments. This may urge them to be inclined to adopt ideas and perceptions, link incidents, and decide upon results without fully investigating the introductions. The opportunities for that spread increase in the presence of conspiracy incubators, such as information misinformation, and mutual accusations between countries about responsibility for spreading the virus, unlike the global conflict that global advocates are establishing about the major conspiracy of entities with interests around the world that may be involved in the conspiracy, and in contrast to these explanations the mentality appears Scientific studies that rely on scientific studies and evidence, and even predict future events in light of specific data, which indicated that the destruction of ecosystems enhances the chances of viruses spreading from animals to humans, especially since they may not find hosts in the environment in which they appear, and the continuation of that environmental destruction may It pushes to the emergence of more fierce pandemics due to the abundance of germs infection and their emergence, and therefore this article is a response to the threat of the recent COVID-19 epidemic, where it emphasizes the role that social science approaches can play in assessing the causes of risks and different trends in their interpretation through rational approaches in understanding the phenomenon Avoid conspiratorial approaches."
Keywords: الفرضيات الجدلية -- فيروس كورونا "كوفيد-19" -- النظرية الإيكولوجية -- الحرب البيولوجية -- الجغرافيا الاقتصادية